Application of two segmentation protocols during the processing of virtual images in rapid prototyping: ex vivo study with human dry mandibles - Ferraz, Eduardo Gomes; Safira Andrade, Lucio Costa; Santos, Aline Rode dos; Torregrossa, Vinicius Rabelo; Fischer Rubira-Bullen, Izabel Regina [UNESP]; Sarmento, Viviane Almeida (Springer, 2013)
The aim of this study was to evaluate the accuracy of virtual three-dimensional (3D) reconstructions of human dry mandibles, produced from two segmentation protocols (outline only and all-boundary lines).Twenty virtual three-dimensional (3D) images were built from computed tomography exam (CT) of 10 dry mandibles, in which linear measurements between anatomical landmarks were obtained and compared to an error probability of 5 %.The results showed no statistically significant difference among the dry mandibles and the virtual 3D reconstructions produced from segmentation protocols tested (p = 0,24).During the designing of a virtual 3D reconstruction, both outline only and all-boundary lines segmentation protocols can be used.Virtual processing of CT images is the most complex stage during the manufacture of the biomodel. Establishing a better protocol during this phase allows the construction of a biomodel with characteristics that are closer to the original anatomical structures. This is essential to ensure a correct preoperative planning and a suitable treatment.
Keywords: X-ray computed tomography; Computer-assisted image processing; Three-dimensional imaging; Rapid prototyping